2017
DOI: 10.1038/srep45309
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating Electric Field Measures the Rotation Rate in a Native Rotary Enzyme

Abstract: Rotary enzymes are complex, highly challenging biomolecular machines whose biochemical working mechanism involves intersubunit rotation. The true intrinsic rate of rotation of any rotary enzyme is not known in a native, unmodified state. Here we use the effect of an oscillating electric (AC) field on the biochemical activity of a rotary enzyme, the vacuolar proton-ATPase (V-ATPase), to directly measure its mean rate of rotation in its native membrane environment, without any genetic, chemical or mechanical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Also, from the studies performed by the dielectric spectroscopy technique [50]- [52], it resulted that the stimulation takes place only at certain representative ("sensitive") frequencies. These results are in good agreement with the results of the in-depth studies reported [53].…”
Section: Stimulation Of Microbial Activity By Elf Electromagnetic Fieldsupporting
confidence: 92%
“…Also, from the studies performed by the dielectric spectroscopy technique [50]- [52], it resulted that the stimulation takes place only at certain representative ("sensitive") frequencies. These results are in good agreement with the results of the in-depth studies reported [53].…”
Section: Stimulation Of Microbial Activity By Elf Electromagnetic Fieldsupporting
confidence: 92%
“…The results of recent experimental investigations [41]- [44] suggest that the microbiological activity can also be stimulated by exposing biomass to an extremely low-frequency electromagnetic field (ELF). In this context, we propose the experimental development and implementation of a system to spur the biological treatment stages by exposing the biomass in the ELF field at a specific frequency, according to [41], [42], [54] at the wastewater treatment plant in Romuli.…”
Section: Specific Energy Consumption: Case Analysismentioning
confidence: 99%
“…It is noted that by overlapping an external EMF on the endogenous electric field of biological systems, the field resulting from the vectorial composition of these can influence (favourably or unfavourably) the cellular transport processes of molecules and electrons and, implicitly, the behaviour of the organism. In this context, the effect of a transmembrane AC field in the 1 Hz -10 kHz range on the biochemical activity of a native yeast vacuolar proton-ATPase (V-ATPase) had been reported recently [58], where the externally applied field generally inhibited the enzyme's rotational activity, except for a region peaking around 86 Hz, at which frequency, the field was able to synchronize the steps of ion-pumping in individual enzymes via a hold-and-release mechanism. It has been experimentally found that the 50 Hz electric field stimulates the growth and reproduction (production of spores) of Aspergillus niger [15].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of behaviour could be attributed to different transmembrane ion-transporting proteinse.g. V-ATPase proton pumps, whose rotational rate can be determined by synchronizing the ion-pumping steps of individual enzymes with a transmembrane AC field [58]. Figure 2 shows the evolution of tgδ as function of frequency in the 1-60 Hz range (extension from Figure 1).…”
mentioning
confidence: 99%